2020
DOI: 10.1002/pc.25921
|View full text |Cite
|
Sign up to set email alerts
|

Numerical‐experimental structural instability analysis of composite tubes considering manufacturing parameters and imperfections

Abstract: A numerical‐experimental approach to predict structural instability was developed to analyze thin composite tubes produced by filament winding subjected to external pressure. The divergence between mechanical properties characterized through standardized procedures and those of the manufactured component, influenced by imperfections and manufacturing peculiarities, was considered. A ring compression test and an inverse finite element analysis routine were used for material properties calibration. The routine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Gerhardt et al did numerical‐experimental instability analyses on filament‐wound rings and found a significant influence of imperfections (eigen buckling) on the mechanical stability during pressure tests. [ 18 ]…”
Section: State Of the Artmentioning
confidence: 99%
“…Gerhardt et al did numerical‐experimental instability analyses on filament‐wound rings and found a significant influence of imperfections (eigen buckling) on the mechanical stability during pressure tests. [ 18 ]…”
Section: State Of the Artmentioning
confidence: 99%
“…Therefore, experimental studies are mostly appealed way to find post-buckling strength. [22][23][24][25][26][27][28] Experimental searches not only help to determine the crippling, but also it provides to specify the effecting parameters of the crippling strength and improve an understanding for the mechanics of the composite structures under the effect of compressive loads. In general, it is possible to gather the influential factors in three groups as geometrical effects, [29][30][31][32][33][34] material, [35][36][37][38][39] and boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is impossible to express a direct relationship between extensional stiffness and bending stiffness for composites with only one equation. Therefore, experimental studies are mostly appealed way to find post‐buckling strength 22–28 …”
Section: Introductionmentioning
confidence: 99%